التقدير القياسي لدالة عرض القمح في ليبيا باستخدام نموذج نيلوفر للتعديل الجزئي خلال الفترة 1994-2023 (Comprehensive Journal of Science, 2026)
The research aimed to identify The lay down the correct scientific foundations to determine the quantities offered of wheat and reduce the waste of it as much as possible, and to reduce dependence on import to provide the food needs of this commodity and to identify the problems and obstacles facing wheat production ,By estimating the two function of supply the wheat commodity in Libya, by describing the economic factors and variables that affect this supply and its trends, The study was reliance on the published and unpublished secondary data sources. This study relied on statistical analysis from both descriptive and quantitative terms through some simple statistical models and econometric statistical that include simple regression analysis in different forms and multiple regression to estimate the function of wheat supply and imports in Libya during the period 1995-2024. The results of the standard analysis of the wheat supply function (the double logarithmic function) showed that it was positively affected by both the price of wheat for the current year and the previous year and the time factor, and it was negatively affected by both the prices of barley for the current year and the previous year.     The study found that the elasticity of the supply of wheat resulting from its price during the same year amounted to about (0.198) and this is showed that the supply of this commodity is inelastic, and the price elasticity of supply resulting from its price for the previous year reached (0.799), which is also inelastic, but the price effect is more visible. Than the first elasticity. the value of the price elasticity of supply in the short run indicates that the response of the total production from the wheat crop to the change in the price of the wheat crop is inelastic, that is, the increase in the price of the wheat crop by 1% leads to an increase in the quantity of the wheat crop at a rate of (1.078%). Also, the price elasticity of supply in the long run indicates that it is as a
Keywords: Supply function - Price elasticity of supply - Wheat